Accuracy Between CURB-65 Score and PSI in Determining The Prognosis of Community-Acquired Pneumonia Patients at H. Adam Malik General Hospital, Medan - Fransisco Sentosa Pakpahan; Syamsul Bihar; Fajrinur Syarani; Putri Chairani Eyanoer (Indonesian Society of Respirology (ISR), 2021)
Background: Community-Acquired Pneumonia (CAP) is an important problem associated with morbidity and mortality. An accurate initial assessment is required before starting management of a CAP patient to determine the prognosis of the patient as early as possible. The CURB-65 score and PSI (Pneumonia Severity Index) are initial assessment scores that can be used. This study aimed to compare the accuracy between the CURB-65 score and the PSI in determining the prognosis in CAP patients at H. Adam Malik General Hospital Medan. Method: A descriptive study was conducted on 76 patients diagnosed with CAP. Each patient was assessed for their CURB-65 score, PSI class and mortality within 30 days of admission. Data were collected through patient medical records diagnosed CAP in 2018 and performed statistical analysis using 2x2 tables. Results: The CURB-65 ≥3 score showed accuracy (71.0%), sensitivity (53.8%), and specificity (89,2%). The CURB-65 ≥ 2 score showed accuracy (75.0%), sensitivity (82.1%), and specificity (67.6%). Meanwhile, the Class IV-V PSI showed accuracy (77.6%), sensitivity (87.2%) and specificity (67.6%). Conclusion: The accuracy of the PSI is higher when compared to the CURB-65 score in determining the prognosis of CAP patients at H. Adam Malik General Hospital Medan. Although PSI is more accurate, CURB-65 is simpler, easier and less expensive to use